WNT5a export onto extracellular vesicles studied at single-molecule and single-vesicle resolution - Schubert, Antonia; Mongkolsittisilp, Ajaree; Kobitski, Andrei Yu.; Schulz, Matthias; Voloshanenko, Oksana; Schaffrinski, Meike; Winkler, Nadine; Neßling, Michelle; Richter, Karsten; Kranz, Dominique; Nienhaus, Karin; Jäger, Dirk; et al. (The FEBS journal, 2025)
WNT signaling governs development, homeostasis, and aging of cells and tissues, and is frequently dysregulated in pathophysiological processes such as cancer. WNT proteins are hydrophobic and traverse the intercellular space between the secreting and receiving cells on various carriers, including extracellular vesicles (EVs). Here, we address the relevance of different EV fractions and other vehicles for WNT5a protein, a non-canonical WNT ligand that signals independently of beta-catenin. Its highly context-dependent roles in cancer (either tumor-suppressive or tumor-promoting) have been attributed to two distinct isoforms, WNT5a Short (WNT5aS) and WNT5a Long (WNT5aL), resulting from different signal peptide cleavage sites. To explore possible differences in secretion and extracellular transport, we developed fusion constructs with the fluorescent proteins (FPs) mScarlet and mOxNeonGreen. Functional reporter assays revealed that both WNT5a isoforms inhibit canonical WNT signaling, and EVs produced by WNT5a-bearing tumor cells, carrying either of the WNT5a isoforms, induced invasiveness of the luminal A breast cancer cell line MCF7. We used fluorescence intensity distribution analysis (FIDA) and fluorescence correlation spectroscopy (FCS) to characterize at single-molecule sensitivity WNT5aL-bearing entities secreted by HEK293T cells. Importantly, we found that most WNT5aL proteins remained monomeric in the supernatant after ultracentrifugation; only a minor fraction was EV-bound. We further determined the average sizes of the EV fractions and the average number of WNT5aL proteins per EV. Our detailed biophysical analysis of the physical nature of the EV populations is an important step toward understanding context-dependent WNT cargo loading and signaling in future studies.